Penerapan Matriks Boston Consulting Group untuk Penanganan Muatan Barang Berbahaya pada Kapal Barang Nasional - Tatiana, Yana; Sari, Darmika; Ricardianto, Prasadja; Malisan, Johny (Institut Transportasi dan Logistik Trisakti, 2024)
The main problem of the research lies in the lack of training, competencies and skills of the crew due to the lack of discipline and the understanding of marine matters, especially related to dangerous goods handling on board. The purpose of the study is to analyze the position and management strategies offered in handling dangerous cargo, especially explosives on board of Sinar Palaran ship. The method to analyze the data was using Boston Consulting Group (BCG) Matrix analysis tool. The result shows that the intensity of dangerous goods cargo mishandling increase. Based on the analysis of Boston Consulting Group Matrix, the position of Sinar Palaran Ship is in Quadrant I, which indicates the company is facing the problem of low competence of the ship’s crew in handling dangerous goods cargo. The strategy offered through BCG Matrix is the strategy to develop, build and increase the intensity of training, discipline and maritime education for crew members to improve their competencies and skills in handling dangerous goods cargo.